Application of the Project Based Learning (PjBL) Learning Model to Improve Students' Critical Thinking Abilities in Science Subjects - Nurdin Muhamad; Tea Nida Na’afilah; Anton (Al-Madrasah: Jurnal Pendidikan, Pembelajaran dan Kebudayaan, 2024)
This research aims to determine the implementation and improvement of students' critical thinking abilities in science learning by implementing the project based learning (PjBL) learning model in class 5 of SDN Kersamenak 1 Garut. In this research, the method used was experimental quantitative research with the sample in this research involving all grade 5 students. The sample in this research involved all grade 5 students with data collection techniques used pretest-posttest, questionnaires and documentation. The results of this research show that the application of the Project Based Learning (PjBL) model can improve students' critical thinking skills in science learning. To see an increase in students' critical thinking abilities in science learning, this can be seen from students' critical thinking abilities using the application of the Project Based Learning (PjBL) model in class V at SDN Kersamenak 1. In the pretest results, they got an average score of 49.1 while the The average posttest result is 84.8 so it can be concluded from the results of the pretest and posttest comparison that there is an increase in students' critical thinking abilities. There are also N-Gain test results which show a figure of 0.71, which means high value.